Loquat – Potential subtropical fruit - Bons, Harsimrat K (Indian Horticulture, 2019)
Loquat or Japanese plum introduced from China has good potential and can be grown in subtropical regions of India. It is one of the few fruits available in March-April and can earn good returns. In addition to fresh consumption, the loquat fruit has good scope for processing and can be processed into number of products like jam, jelly squash, osmodehydrated products etc. Apart from excellent nutritional value, it has good medicinal value also. There is an urgent need to extend the area under this crop which will be helpful in diversifying the fruit cultivation.